Imaging method for airborne SAL data. Issue 5 (1st March 2017) - Li, Guangzuo; Wang, Ning; Wang, Ran; Zhang, Keshu; Wu, Yirong
Abstract : Synthetic aperture ladar (SAL) is analogous to the synthetic aperture radar (SAR) but works at wavelength 10 4–5 times shorter. SAL has the potential for much finer resolution than SAR. Due to the shorter wavelength used for SAL, the platform vibration would induce high‐frequency and large‐amplitude phase errors during the data collection. Direct using of the conventional imaging algorithms to SAL data suffers from performance degradation. To address this problem, an effective imaging method based on subaperture phase gradient autofocus (PGA) and normalised cross correlation (NCC) is proposed for airborne SAL data. First, the length of subaperture is determined according to the criterion that the coherent processing interval (CPI) is shorter than half of the vibration period. Then the phase history data (PHD) is formatted into a few subapertures and the PGA is employed to estimate the phase errors in each subaperture. After the compensation of the phase errors, each subaperture image is focused with the conventional imaging algorithm. Finally, a recombination of the subapertures is performed based on the NCC. The proposed method is verified by processing the real SAL data collected by strip‐mode with the demonstrator system built at Institute of Electronics, Chinese Academy of Science.